South Sumatra Local Culture-Based Teaching Materials Training for Vocational School Language Teachers - Inderawati, Rita; Amrullah, Amrullah; Sofendi, Sofendi; Mirizon, Soni; Purnomo, Mulyadi Eko; Ernalida, Ernalida; Indrawati, Sri; Shilviany, Sary; Alwi, Zahra (ENGLISH FRANCA : Academic Journal of English Language and Education, 2022)
This article reported a training conducted to increase competency mastery of teachers of Bahasa Indonesia and English in vocational schools in Palembang in developing teaching materials based on the local culture of South Sumatra. Applying the development research method, the following stages were conducted: Â identifying goals and objectives, conducting instructional analysis, determining entry behavior and student characteristics, writing performance objectives, developing assessments of teaching materials that refer to criteria, and developing texts of teaching materials. The training was conducted in the form of lectures, questions and answers, discussions, and demonstrations. The product of this training was teaching materials with the readings that were based on the local culture of South Sumatra.